Pengaruh Gaya Kepemimpinan Transformasional Terhadap Produktivitas Kerja Karyawan PT. Sinar Citra Harapan Kabupaten Maros - Ragil Aditya; Siti Hasbiah; Agung Widhi Kurniawan (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This study aims to determine the effect of transformational leadership style on employee productivity at PT Citra Sinar Harapan Maros Regency. This type of research is quantitative As for the population with a total of 100 employees with a sample obtained of 50 employees at. The sampling technique used uses the slovin formula. The data collection technique was carried out by distributing questionnaires to employees. The data analysis technique uses simple regression with the help of SPSS software version 25. The results of this study indicate that transformational leadership style has a significant positive effect on employee work productivity at PT Citra Sinar Harapan Maros City. This can be proven based on the regression analysis obtained a constant value of 13.686 and a regression coefficient X of 0.626 and a coefficient of determination (R2) of 0.324 or (32.4%).